Processo de criação em arte: estudo de caso do artista plástico e professor Nelson Leirner - Paste, Rosana Lucia (2010)
It’s about the art creating process on the installation Vestidas de Branco (Dressed in White), held at Vale Museum in 2008, by Nelson Leirner an artist from São Paulo. It’s an artistic proposition based on the account of his process of creation and on the development of his creative capacity through an active look of the world. It studies the process of creation in arts by other artists as aesthetic experience and awareness for the development of the creative process from who creates it. It evaluates the importance of the method which shall be created from the study of case to be defined and it observes the Genetics criticism as a theoretical support for this study. The phenomenological observation, description, and analysis were criteria used here. It observes the means through which the artist elects as part of his process for the development of his work in arts. It describes the stages which allow the changing of living structures and his existing repertoire as part of the creative process. It analyses how the object of art goes through changes until it’s seen by the public without having access to it.